Hubungan Antara Kebiasaan Membaca dengan Hasil Belajar Siswa Kelas V SDN Gugus X Kota Bengkulu - Destiyanti, Liana; Muktadir, Abdul (JURIDIKDAS, 2026)
This Study aims to determine the relationship between reading habits and learning outcomes of fifth grade students at SDN Gugus X Bengkulu City. The type of research used is quantitative with correlation research methods. The population of this study were all fifth grade students at SDN Gugus X Bengkulu City, totaling 89 students. The sample for this research was the fifth grade students at SDN Gugus X Bengkulu City who were taken by total sampling technique. The research instrument used was a questionnaire. Data collection techniques using questionnaires and documentation. The data analysis technique in this study uses the Pearson product moment correlation calculation. The results showed that the correlation coefficient was 0.949 with a significance level of 5% and n = 89, so the was 0.208. Thus, it is obtained that > , which is 0.949 > 0.208, with the contribution of variable X to variable Y of 90.1%. It can be concluded that there is a relationship between reading habits and learning outcomes of class V students at SDN Gugus X Bengkulu City with the level of correlation between the variable reading habits (X) and learning outcomes (Y) in the very strong category.